Screening and Control of Non-Communicable Diseases (NCD) Through Empowerment of Cadres and Health Personnel in Kalasey II Village, Minahasa Regency - Djaafar, Nurseha Salat; Kolompoy, Jane Anita; Memah, Herlina P (JURNAL PENGABDIAN MASYARAKAT KOMUNITAS KESEHATAN, 2024)
Non-communicable diseases (NCDs) are a health problem that has become a national and global concern. NCD morbidity and mortality is increasing in Indonesia. According to the World Health Organization (WHO), it shows that of the 57 million deaths in the world in 2008, the majority were caused by NCDs, and continue to increase throughout the world, the largest increase occurring in middle and poor countries. About 70% of the global population will die from NCDs. Health problems in the elderly are related to non-communicable diseases (NCDs), namely obesity, hypertension, diabetes mellitus. This activity aims to increase knowledge and target partner services regarding screening for prevention and control of NCDs, through posbindu services in Kalasey II village, Mandolang subdistrict in the elderly group (45 -59 years) and detection of NCD risk factors, Increase communication capacity between health workers, between lecturers as well as between posbindu cadres, increasing the role of elderly people who are targeted by partners to participate in screening for early detection and control of NCDs. This activity was carried out in Kalasey Village 2, Mandolang sub-district, Minahasa Regency. This series of activities will be carried out for three months, namely July - September 2023. The solution to the problems offered in this community service activity is screening and educational outreach regarding prevention of accelerated control of NCDs (Hypertension, Diabetes Mellitus, Obesity, Hypercholesterol, and Hyperuresemia) through Posbindu. The methods of this activity are screening examinations, posbindu simulations, and assistance to the elderly target group, totaling 94 people. The achievement targets are Health Screening services for the Elderly (45-59 years) and > 60 years as much as 78%, Screening and services for Hypertension sufferers 85%, Screening and control services for Cholesterolemia sufferers 80%, and Screening services for the elderly with Diabetes Mellitus 35%, Screening and Hyperuresemia control services 47%, Screening services for obese elderly. The output achieved is the mandatory output targeted is the publication of the Community Service journal. Target TS: Submit T +1: Accepted. and additional output, namely: IPR Implementation Methods for Community Service.